Coordinated reactive power optimization for multi-TSO grids in an autonomous way. Issue 5 (5th September 2016) - Zhang, Anan; Chen, Shi; Zhang, Fan; Zhang, Xuliang; Li, Hongwei; Gong, Xue
Abstract : Purpose: It is very indispensable for the various control centers of multi-transmission system owners (TSOs) grids to coordinate their reactive power optimization (RPO) efforts. However, such coordinated equilibrium point is comparatively hard to achieve unless one TSO control center could obtain all grids' information in detail, which may lead to confidential issue and heavy communicating load. The purpose of this paper is to propose a solution to optimizing the reactive power control efforts among multi-TSOs grids with a mathematic interconnection model and reasonable communication cost. Design/methodology/approach: Based on the interconnected power network equation, the stability-related optimum reactive power injection and the power-loss-related optimum reactive power injection were derived, respectively. Furthermore, according to the decomposition-and-coordination-based computing methodology, a coordinated RPO model for interconnected TSOs was designed, taking into consideration both the static voltage stability and economy. Findings: The extreme values for the indicator L of power grid voltage stability and active power loss function were found and proved to be minimums. According to these extreme values, an expression for the reactive power injection at interconnected nodes between TSOs grids was obtained, and a coordinated strategy of RPO was established, which could take the static voltage stability and economy into consideration without confidential concern. Originality/value: The existence of minimum values for indicator L of voltage stability and power loss was demonstrated, respectively. And the method presented in this paper can ensure the safety of information among different TSO grids, i.e. avoiding confidential issues. In particular, the coordinated control method can be implemented on the local power grid without knowing all of the parameters of its interconnection.